Postpartum haemorrhage and synthetic oxytocin dilutions in labour. (2nd October 2021) - Tolofari, Monica; Shepherd, Linn
Abstract : This study investigated postpartum haemorrhage and historic oxytocin usage, because haemorrhage rates are rising. During the evolution of practice from intravenous bovine post-pituitary extract to synthetic oxytocin, experimental interventions had produced improved outcomes in certain cases and the postpartum haemorrhage rate was low. In this study, current synthetic oxytocin regimes from across the UK were compared with the 1977 (unchanged) licensed instructions for infusion. As a result of the pain-inducing properties of synthetic oxytocin, epidural analgesia prior to infusion is now standard for unlicensed regimes, adding complexity to intrapartum care and greater risks of complex births, as the fetus may be adversely affected by epidural drugs and acidosis. Unlicensed synthetic oxytocin dilutions and increments, the desensitising of oxytocin receptors, and unmeasured error factors in infusion pumps affect labour progress and outcomes. Today's rates of postpartum haemorrhage are associated with these changes to obstetric practice. Failure to inform women of intended unlicensed practices with synthetic oxytocin, or obtain consent for such, or offer licensed practice as standard constitutes neglect of the legal obligations outlined for doctors and midwives by professional Codes of Practice, intended to protect patients from predictable dangers.